2020
DOI: 10.1007/jhep11(2020)109
|View full text |Cite
|
Sign up to set email alerts
|

LHC signals for KK graviton from an extended warped extra dimension

Abstract: We analyze signals at the Large Hadron Collider (LHC) from production and decay of Kaluza-Klein (KK) gravitons in the context of “extended” warped extra-dimensional models, where the standard model (SM) Higgs and fermion fields are restricted to be in-between the usual ultraviolet/Planck brane and a ∼ O(10) TeV (new, “intermediate”) brane, whereas the SM gauge fields (and gravity) propagate further down to the ∼ O(TeV) infrared brane. Such a framework suppresses flavor violation stemming from KK particle effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Collider physics of radions, KK gravitons and KK gluons are also important subjects in models defined on a higher dimensional spacetime [76,77]. For instance, KK gluons mediate dijet and t t production processes at hadron colliders.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Collider physics of radions, KK gravitons and KK gluons are also important subjects in models defined on a higher dimensional spacetime [76,77]. For instance, KK gluons mediate dijet and t t production processes at hadron colliders.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…, have profiles localized to the intermediate brane at z = z 1 , they have sizable coupling with the dark U(1) D gauge boson A (1) D . 23 If T R ∼ Λ 1 (but less than confinement phase transition temperature), these KK modes can be excited and can easily populate the dark sector. If T R Λ 1 , they are not produced cosmologically; leaving only the zero mode, B (0) µ , (i.e.…”
Section: Jhep03(2023)172mentioning
confidence: 99%
“…An interesting signature is the four-jet final state stemming from the processes, G KK → ϕϕ, ϕ → gg (called "radion channel") and G KK → gg KK , g KK → gϕ, ϕ → gg (called "KK gluon channel"), with G KK and g KK denoting the lightest KK graviton mode and the lightest KK gluon mode, respectively (see Figure 7). These channels become more significant especially in the model variation where the SM gluon field is propagating in the extended bulk while the propagation of EW fields is restricted to the Higgs brane [17] (see Figure 8), in part because radion decays to di-photon (golden channel) are then extremely suppressed. Depending on the underlying mass spectrum, one channel is leading to the other, and different search strategies are motivated due to the difference of the associated event topologies.…”
Section: Four-jet Signals Of Kk Gravitonmentioning
confidence: 99%
“…Depending on the underlying mass spectrum, one channel is leading to the other, and different search strategies are motivated due to the difference of the associated event topologies. We have performed a sensitivity study with a few well-motivated benchmark sets of parameter values giving well-separated four jets, and found that the HL-LHC (3,000 fb −1 ) would be sensitive to the KK graviton signals by ∼ 2.5 − 5σ significance [17]. It was further found that the radion channel can be the first discovery channel of KK graviton due to the effectiveness of the cuts designed for the event topology of the radion channel signal, while the KK gluon channel can serve as a cross-check to understand the structure of the underlying model.…”
Section: Four-jet Signals Of Kk Gravitonmentioning
confidence: 99%
See 1 more Smart Citation